PERAN INTERNATIONAL FUND FOR AGRICULTURAL DEVELOPMENT (IFAD) DALAM MENINGKATKAN KETAHANAN PANGAN DI PROVINSI MALUKU UTARA MELALUI PROGRAM SMALLHOLDER LIVELIHOOD DEVELOPMENT PROJECT (SOLID) IN EASTERN INDONESIA 2011-2019 - Adelia Pradana Putri Prasetya (2023)
Indonesia is an agricultural country with most of its people working as farmers who have great potential to become one of the world's producers of various agricultural products. However, Indonesia's wealth of natural resources is not in line with the capacity of its human resources. This makes Indonesia to still be one of the countries with a low level of food security, especially in rural areas in Eastern Indonesia. One of the ways to overcome these problems is through cooperation between the government and international organizations, such as with IFAD Indonesia through the Smallholder Livelihood Development Project (SOLID) in Eastern Indonesia 2011-2019 which focuses on improving people's welfare, so that food security can be achieved. This study uses descriptive research methods with data collection techniques obtained through primary data sources and secondary data. Researchers analyzed the data that had been obtained using the concept of food security and the theory of the role of international organizations according to Clive Archer. The results of the study show that IFAD Indonesia has played a significant role in increasing food security in Eastern Indonesia through several of its programs, such as organize and develop a self-help groups and federation, easy access to loans, technology and markets, farmers field school program, gender inclusiveness, infrastructure development, and encouraging simple value chains and long value chains. After being analyzed using Clive Archer's theory, IFAD Indonesia has carried out its function as an international organization by becoming an instrument, arena, and independent actor in helping Indonesia to overcome food insecurity.